Prosthodontic Management of Maxillary Flabby Ridge - A Case Report - Kumar Karna, Nishesh; Babu Basnet, Bishal; Kumar Parajuli, Prakash; Suwal, Pramita (Journal of Nepalese Prosthodontic Society, 2025)
Complete denture prosthesis replaces the lost teeth and associated structure of oral cavity. Success of complete denture depends upon various factors among which health of underlying denture bearing area is of utmost importance. Any departure from health of denture bearing area in the form of inflammation, ulceration, resorption, hyperplastic tissue to name a few will adversely affect the overall prognosis of denture. Flabby ridge is a common clinical scenario which must be addressed during denture fabrication. Efforts have been undertaken both surgically and conservatively to accommodate this flabby tissue. This case report describes one of the conservative methods wherein modification in impression making using conventional impression material was attempted.